Metallurgical assessment of Al-Zr-Y alloys for laser-based processing - J.T. Hierlihy; I.W. Donaldson; D.P. Bishop (Journal of Alloys and Metallurgical Systems)
The scope of aluminum alloys commercially available for laser-based additive manufacturing is limited yet the demand for them is growing aggressively. In many cases, end-users are particularly interested in those that offer enhanced thermal stability. Historically, several such materials were premised on alloys that incorporated transition metal (TM) additions which formed refractory aluminides as the principal strengthening addition. The objective of this study was to pursue a similar concept but as applied to the ternary Al-Zr-Y alloy system. In doing so, plates with varying Zr and Y contents (0–2 wt%) were cast and subsequently subjected to laser remelting (LRM) using a Yb-fibre laser. Microstructures then characterized using laser confocal microscopy, XRD, SEM, and TEM. LRM was seen to produce an epitaxial columnar α-Al matrix in binary Al-Y alloys, with intergranular solidification cracking seen in the highest Y content of 2 wt%. In Al-Zr specimens, increasing Zr content resulted in the development of a duplex microstructure consisting of distinct epitaxial columnar regions near the melt pool boundary and equiaxed regions near the center. The development of equiaxed regions was ascribed to the presence of sub-micron dispersoids. These dispersoids were Zr-rich and increased in number with corresponding increases in Zr content. They were also observed in Al-Zr-Y specimens and were subsequently identified as an L12-Al3Zr. The addition of Y produced a dramatic increase in dispersoid density, and consequently the proportion of equiaxed grains, demonstrating that the Al-Zr-Y system is a promising candidate for laser-based processing technologies.